2015
DOI: 10.1016/j.chembiol.2015.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Structuring Microbial Metabolic Responses to Multiplexed Stimuli via Self-Organizing Metabolomics Maps

Abstract: Secondary metabolite biosynthesis in microorganisms responds to discrete chemical and biological stimuli; however, untargeted identification of these responses presents a significant challenge. Herein we apply multiplexed stimuli to Streptomyces coelicolor and collect the resulting response metabolomes via ion mobility-mass spectrometric analysis. Self-organizing map (SOM) analytics adapted for metabolomic data demonstrate efficient characterization of the subsets of primary and secondary metabolites that resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…Secondary metabolite production can be activated in microorganisms through a variety of chemical and environmental stimulation, 29,30,183,184 and PCA and PLS are commonly applied to identify abundantly produced features in these conditions. 40,185-187 Binary comparisons using S-plots can be a used to identify group specific features of a PLS model.…”
Section: Analysis Of Metabolomics Data In the Context Of Secondary mentioning
confidence: 99%
See 2 more Smart Citations
“…Secondary metabolite production can be activated in microorganisms through a variety of chemical and environmental stimulation, 29,30,183,184 and PCA and PLS are commonly applied to identify abundantly produced features in these conditions. 40,185-187 Binary comparisons using S-plots can be a used to identify group specific features of a PLS model.…”
Section: Analysis Of Metabolomics Data In the Context Of Secondary mentioning
confidence: 99%
“…For instance, it is common to screen a target organism under dozens of stimulus conditions to optimize compound production, or to induce silent biosynthetic gene clusters, and in these cases we have previously demonstrated that an alternative method utilizing Kohonen self-organizing map (SOM) analytics can be more effective at representing multiplexed stimuli data than PCA. 184 As discussed above, metabolomic acquisition via LC-MS results in the acquisition of thousands of detectable features. Through SOM analyses these features are organized using an artificial neural network into a 2-dimensional grid based on feature response patterns across all experimental conditions.…”
Section: Analysis Of Metabolomics Data In the Context Of Secondary mentioning
confidence: 99%
See 1 more Smart Citation
“…SOM differential analysis allows numerous comparisons between SOMs originating from discrete samples and/or time points of the experiment. Another benefit of the SOM approach is the ability to “decrypt” specific nodes on the map to extract primary feature information, such as retention time and m/z (148,149). A recent example of using SOMs to systems-level mapping of molecules is contained in Figure 8 for an “organ-on-chip” human liver bioreactor exposed to acetaminophen (APAP) (150).…”
Section: Novel Strategies For Visualizing Big Datamentioning
confidence: 99%
“…Self-organizing data techniques and MEDI approaches have been used to rapidly characterize molecular indicators of drug addiction phenotype (34) and to prioritize candidate molecules in drug discovery efforts from natural products (39,40). The latter demonstrates a different feature of MEDI maps, namely the ability to perform mathematical operations on the untargeted data to drive further interpretive power.…”
Section: Bioinformatics Of High Dimensional Data For Rapid Target Primentioning
confidence: 99%